2019
DOI: 10.1177/1535370218823684
|View full text |Cite
|
Sign up to set email alerts
|

Plasma NAP-2 levels are associated with critical limb ischemia in peripheral arterial disease patients

Abstract: Our study evaluates the relationship between plasma neutrophil-activating peptide-2 (NAP-2) levels and critical limb ischemia (CLI); 189 subjects were enrolled in this study: 59 subjects with CLI and type 2 diabetes mellitus (T2DM), 45 subjects with CLI and no T2DM, 43 patients with T2DM and no CLI, and 42 without both T2DM and CLI. Subjects with CLI had higher plasma levels of NAP-2 than those of the healthy group (2.04 ± 0.06 ng/mL vs. 1.75 ± 0.09 ng/mL, P = 0.011). Subjects with CLI and T2DM had higher plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In the study of Ku et al [ 31 ], upregulated NAP2 was significantly associated with severity of coronary artery stenosis in patients with diabetes. Recently Wang et al showed that elevated plasma NAP2 level was independently associated with critical limb ischemia, not with diabetes [ 32 ], however a connection with the walking capacity was not considered. Until now the deregulation of GRO was never shown before in the context of PAD.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Ku et al [ 31 ], upregulated NAP2 was significantly associated with severity of coronary artery stenosis in patients with diabetes. Recently Wang et al showed that elevated plasma NAP2 level was independently associated with critical limb ischemia, not with diabetes [ 32 ], however a connection with the walking capacity was not considered. Until now the deregulation of GRO was never shown before in the context of PAD.…”
Section: Discussionmentioning
confidence: 99%
“…Stable angina patients had markedly higher plasma levels of NAP-2 and increased expression of the monocyte CXCR2 compared to healthy controls [16]. Elevated NAP-2 levels have also been reported in patients with critical limb ischemia [17], antiphospholipid syndrome (APS) [18], and colorectal cancer [19,20]. Increased expression of genes related to platelet activation, including PPBP/CXCL7, has been shown in coronavirus disease 2019 (COVID-19) patients [21].…”
Section: Introductionmentioning
confidence: 99%
“…Stable angina patients had markedly higher plasma levels of NAP-2 and increased expression of the monocyte CXCR2 compared to healthy controls [ 16 ]. Elevated NAP-2 levels have also been reported in patients with critical limb ischemia [ 17 ], antiphospholipid syndrome (APS) [ 18 ], and colorectal cancer [ 19 , 20 ]. Increased expression of genes related to platelet activation, including PPBP/CXCL7 , has been shown in coronavirus disease 2019 (COVID-19) patients [ 21 ].…”
Section: Introductionmentioning
confidence: 99%